Is Halal Certification Process Ã¢â‚¬Å“GreenÃ¢â‚¬Â? - Razalli, Mohd Rizal; Abdullah, Suzzaini; Yusoff, Rushami Zien (The Asian Journal of Technology Management (AJTM), 2012)
These days, the environmental perspective on operations is becoming more common. In fact, any effort in improving efficiency in the organization is closely related to sustainability of our environment. The Environmental Management System (EMS) certification such as ISO 14001 has been accepted as the world standard. In addition to these ISO standards, there are other certifications such as Halal certification. There is no research that investigates the relationship between Halal Certification process and its effect on our environment. Hence, our main research question is that is Halal Certification process can be considered as environmental friendly? In this paper, we argue that Halal Certification also contributes towards green initiatives. We used EDC-UUM as our case study. EDC-UUM is actively seeking the Halal certification from Malaysian authority agency or JAKIM. In this study, we assessed the perception of the EDC-UUM staff on the issue of going green. The findings and implications are discussed in the paper. Keywords: halal certification, hotel operations, sustainability, green